Control of fluid intake in dehydrated rats and evolution of sodium appetite - De Luca, Laurival A. [UNESP]; Laurin, Michel; Menani, José Vanderlei [UNESP] (Elsevier, 2024)
The objective of the present work is to examine from a new perspective the existence of causal factors not predicted by the classical theory that thirst and sodium appetite are two distinct motivations. For example, we ask why water deprivation induces sodium appetite, thirst is not “water appetite”, and intracellular dehydration potentially causes sodium appetite. Contrary to the classical theory, we suggest that thirst first, and sodium appetite second, designate a temporal sequence underlying the same motivation. The single motivation becomes an “intervenient variable” a concept borrowed from the literature, fully explained in the text, between causes of dehydration (extracellular, intracellular, or both together), and respective behavioral responses subserved by hindbrain-dependent inhibition (e.g., lateral parabrachial nucleus) and forebrain facilitation (e.g., angiotensin II). A corollary is homology between rat sodium appetite and marine teleost thirst-like motivation that we name “protodipsia”. The homology argument rests on similarities between behavior (salty water intake) and respective neuroanatomical as well as functional mechanisms. Tetrapod origin in a marine environment provides additional support for the homology. The single motivation hypothesis is also consistent with ingestive behaviors in nature given similarities (e.g., thirst producing brackish water intake) between the behavior of the laboratory rat and wild animals, rodents included. The hypotheses of single motivation and homology might explain why hyperosmotic rats, or eventually any other hyperosmotic tetrapod, shows paradoxical signs of sodium appetite. They might also explain how ingestive behaviors determined by dehydration and subserved by hindbrain inhibitory mechanisms contributed to tetrapod transition from sea to land.
Keywords: Angiotensin; Hindbrain; Motivation; Teleost; Thirst; Transitional environment